KETERKAITAN KEBIJAKAN LEVERAGE DAN DIVIDEN SERTA FAKTOR YANG MEMPENGARUHINYA PADA PERUSAHAAN YANG LISTED DI BURSA EFEK INDONESIA - Kusnandar, 11.42.02.0044 (Students Journal of Economic and Management, 2013)
This study was conducted to examine the interdepedensi between financial leverage and the dividend payout ratio and the factors affecting them such as investment, profitability, growth and variability of earnings. The sampling technique used was purposive sampling in companies listed on the Indonesia Stock Exchange unless the banks for the period 2008 to 2010. Total sample of 226 acquired firms. The analysis technique used is multiple linear regression equation least squares and test hypotheses using t-statistics for testing the partial regression coefficients and F-statistics to test the significance effect together with the level of significance of 5%. From the results of the analysis indicate that there is no relationship between financial leverage with a dividend payout ratio, profitability significant positive effect on financial leverage and the dividend payout ratio, while investment, growth and variability of earnings does not have a significant effect on both. Level of predictive capability of the five variables are the financial leverage of 6.1% while the remaining 93.9% is influenced by other factors not included in the research model, and the level of predictability of the five variables are the dividend payout ratio of 2.9%, while the remaining 97.1% is influenced by other factors not included in the research model. Keywords : financial leverage, dividend payout ratio, investment, profitability, growth and variability of earnings